R‐based Tool for a Pairwise Structure‐activity Relationship Analysis. Issue 4 (25th October 2017) - Klimenko, Kyrylo
Abstract: The Structure‐Activity Relationship analysis is a complex process that can be enhanced by computational techniques. This article describes a simple tool for SAR analysis that has a graphic user interface and a flexible approach towards the input of molecular data. The application allows calculating molecular similarity represented by Tanimoto index & Euclid distance, as well as, determining activity cliffs by means of Structure‐Activity Landscape Index. The calculation is performed in a pairwise manner either for the reference compound and other compounds or for all possible pairs in the data set. The results of SAR analysis are visualized using two types of plot. The application capability is demonstrated by the analysis of a set of COX2 inhibitors with respect to Isoxicam. This tool is available online: it includes manual and input file examples. Abstract :